Novel Molecular Assay for Simultaneous Identification of Neglected Lungworms and Heartworms Affecting Cats - Di Cesare, Angela (J Clin Microbiol, 2015)
Feline lungworms and heartworms are stimulating the interest of the scientific community due to their clinical impact and apparent geographical expansion. Diagnosis of the infections caused by these nematodes is indeed challenging. This report describes a novel multiplex PCR able to identify simultaneously three species of lungworms (Aelurostrongylus abstrusus and Troglostrongylus brevior) and heartworms (Angiostrongylus chabaudi) affecting felids. Epidemiological and clinical perspectives are discussed.